Nas ondas do mar de óleo: responsabilidade estatal e a reparação dos pescadores artesanais pelos danos decorrentes da poluição por óleo do mar brasileiro em 2019 - Silva, Norma Navegantes da (2024)
The sea is more than an economically exploitable space, it is territory, father, bread and the common home of coastal cultures and peoples. For this reason, when disasters occur in the marine environment, the damage takes on multiple and complex dimensions and needs to be repaired. In 2019, the most extensive environmental disaster in Brazil's history occurred, consisting of an oil spill that affected the entire northeastern coast of the country. The pollution of marine ecosystems caused environmental, socio-economic and cultural damage to the livelihoods of Traditional Fishing Communities, which to this day has not been repaired. The lack of reparation is mainly due to the lack of accountability of those directly responsible for the pollution, due to the failure to identify the exact origin of the spill. Faced with this situation of environmental injustice, this paper is dedicated to studying the possibility of holding the state responsible for its omissions in the process of mitigating the effects of marine oil pollution, through a bibliographical review of secondary sources and documentary research into laws, decrees and court decisions on the issues surrounding the problem. To this end, the dimensions of the damage caused by the oil spill incident on the Brazilian coast were identified, through the chronology of state actions and the effects of pollution on the way of life of the people of the sea. Subsequently, state responsibility for damage resulting from economic activities carried out by third parties was explained, based on internal legal rules protecting the environment and court decisions on similar cases. Finally, the ongoing injustice against artisanal fishing was briefly demonstrated, as well as analyzing how class actions can be an instrument for protecting the transindividual interests of artisanal fishermen, identifying the legal foundations capable of deconstructing part of the barriers to these workers' access to blue environmental justice. In conclusion, it was noted that it is possible to hold the Federal Government civilly liable for the damage caused to Traditional Fishing Communities, due to the negligence with which it conducted the contingency actions in 2019. This collective claim must be promoted and conducted from the perspective of the structural process, guaranteeing, in addition to compensation, a judicial provision that promotes the improvement of public policies linked to the protection of artisanal fishing and the environment against new disasters at sea.